Multi-Cellular Activation In Vivo by Endotoxin in Humans – Limited Protection by Adenosine Infusion - Li, Nailin; Soop, Anne; Sollevi, Alf; Hjemdahl, Paul (Thrombosis and Haemostasis, 2000)
The influence of adenosine infusion (40 µg/kg/min for 4 h) on inflammatory and hemostatic parameters was investigated in healthy males without (n = 10) or with (n = 11) intravenous endotoxin injection (4 ng/kg). Without endotoxin, adenosine elevated circulating leukocytes and circulating platelet-leukocyte aggregates. Endotoxin activated platelets and leukocytes in vivo. Platelet activation was seen as slightly increased platelet P-selectin expression, decreased platelet counts, and elevated plasma soluble P-selectin (from 39.6 ± 3.4 to 68.9 ± 6.6 ng/ml; P <0.01). Leukocyte activation was evidenced by increased CD11b expression (from MFI of 0.54 ± 0.02 to 2.21 ± 0.17; P <0.01) and plasma elastase levels (from 25.3 ± 2.5 to 169.3 ± 22.5 ng/ml; P <0.01). Endotoxin also enhanced platelet and leukocyte responsiveness to in vitro stimulation. Endotoxin induced von Willebrand factor secretion (from 92 ± 8 units to 265 ± 19 units at 4 h; P <0.001) and enhanced thrombin generation in vivo. Endotoxin induced leukocytosis and thus increased circulating platelet-leukocyte, mainly platelet-neutrophil, aggregates. Adenosine caused slight attenuation of platelet reactivity to agonist stimulation, enhanced the endotoxin-induced leukocytosis, and detained more platelet-leukocyte aggregates in circulation, but did not attenuate endotoxin-induced neutrophil elastase secretion, von Willebrand factor secretion, or thrombin generation. Thus, endotoxemia induces multi-cellular activation in vivo. Adenosine inhibits leukocyte adhesion and extravasation, and mildly attenuates platelet responsiveness and soluble P-selectin release. Adenosine has the potential of becoming a therapeutic antiinflammatory drug, but an optimal treatment strategy needs to be developed.
Keywords: Adenosine; endotoxin; platelets; leukocytes; platelet-leukocyte aggregates